2014
DOI: 10.1002/ajmg.a.36366
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth: The heart of the matter

Abstract: We evaluated 2,083 cases within the Wisconsin Stillbirth Service Program (WiSSP) that had autopsy reports or ultrasound data relevant to the heart. Of these, 167/1,782 (9.4%) stillbirths after 20 weeks and 11/301 (3.7%) miscarriages <20 weeks had congenital heart disease (CHD). Cases were classified by type of heart defect and whether it related to cause of death. Among cardiac anomalies that contributed significantly to fetal death, 125/151 (83%) were associated with underlying conditions or syndromes, nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
1
32
1
1
Order By: Relevance
“…Currently active databases may derive from society-sponsored clinical data registries (eg, the STS Congenital Heart Surgery Database, the American College of Cardiology's Improving Pediatric and Adult Congenital Treatment [IMPACT] Registry), administrative databases (eg, the Pediatric Health Information System), and research databases (eg, the NHLBI's PHN and Pediatric Cardiac Genomics Consortium). Data can also be derived from electronic health records, industry databases for devices, genetics research registries, and consortia of centers dedicated to missions such as quality improvement (eg, the National Pediatric CardiologyQuality Improvement Collaborative) or to specific disciplines within pediatric cardiology (PC 4 ; the Tracking Outcomes and Practice in Pediatric Pulmonary Hypertension [TOPP-2] registry, etc). Additional efforts in linking data across institutions comes from the Cardiovascular Research Network, a consortium linking electronic health records across healthcare systems, which is working to extract data on CHD patients using natural language text processing algorithms in unstructured electronic health records.…”
Section: Cardiac Registries and Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently active databases may derive from society-sponsored clinical data registries (eg, the STS Congenital Heart Surgery Database, the American College of Cardiology's Improving Pediatric and Adult Congenital Treatment [IMPACT] Registry), administrative databases (eg, the Pediatric Health Information System), and research databases (eg, the NHLBI's PHN and Pediatric Cardiac Genomics Consortium). Data can also be derived from electronic health records, industry databases for devices, genetics research registries, and consortia of centers dedicated to missions such as quality improvement (eg, the National Pediatric CardiologyQuality Improvement Collaborative) or to specific disciplines within pediatric cardiology (PC 4 ; the Tracking Outcomes and Practice in Pediatric Pulmonary Hypertension [TOPP-2] registry, etc). Additional efforts in linking data across institutions comes from the Cardiovascular Research Network, a consortium linking electronic health records across healthcare systems, which is working to extract data on CHD patients using natural language text processing algorithms in unstructured electronic health records.…”
Section: Cardiac Registries and Databasesmentioning
confidence: 99%
“…Although there is slight variation between many population-based studies, CHD occurs in ≈1% of live births, with similar prevalence throughout world, [1][2][3] and in 10% of aborted fetuses. 4 It is also the leading cause of mortality from birth defects. 5 Approximately one-quarter of the 40 000 children born with CHD annually in the United States require intervention in the first year of life.…”
mentioning
confidence: 99%
“…The analysis of 167 stillborn infants with heart defects in the Wisconsin Stillbirth Service Program concluded that many heart defects (83%) contributed to the fetal death (Jorgensen et al, ). The most common heart defects were severe cyanotic lesions, such as hypoplastic left heart syndrome and tetralogy of Fallot with pulmonary atresia, and ventricular and atrial septal defects.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of malformations identified in stillborn infants has been described in several systematic studies (Mueller et al, , Pauli, ; Pauli and Reiser, ; Yamauchi et al, ; Botto et al, ; Pinar et al, ; Jorgensen et al, ). Chromosome abnormalities, primarily the trisomies, have been the most common diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation